Association between resilience and cortical thickness in the posterior cingulate cortex and the temporal pole in Japanese older people: A population-based cross-sectional study. (October 2021) - Shikimoto, Ryo; Noda, Yoshihiro; Kida, Hisashi; Nakajima, Shinichiro; Tsugawa, Sakiko; Mimura, Yu; Ochi, Ryo; Takayama, Midori; Niimura, Hidehito; Mimura, Masaru
Abstract: Background: Resilience is a crucial factor preventing the onset of mental illness and contributing to the well-being and healthy longevity, whose neural bases are not fully elucidated in older people. The present study aimed to identify the cortical thickness associating with resilience in older adults. Methods: This is a part of the cross-sectional Arakawa geriatric cohort study for people aged 65 years or older, consisting of 1001 individuals. A Self-Reported Resilience Scale (RS), neuropsychological batteries, face-to-face interviews for diagnosis, and a three-dimensional T1-weighted magnetic resonance imaging were conducted. Cortical thickness was computed by the FreeSurfer. The relationships among cortical thickness, total RS score, and clinico-demographic data were investigated using univariate and multivariable regression analyses. Results: The total RS score was correlated with age, education, and scores of the Mini-Mental State Examination (MMSE) and Geriatric Depression Scale (GDS) in univariate analyses. The total RS score was associated with cortical thicknesses in the left posterior cingulate (β [95 % CI of B] = 0.07 [0.16–14.84]) and the left temporal pole (β [95 % CI of B] = 0.08 [0.63–9.93]) after adjusting sex, age, imaging acquisition site, education, MMSE and GDS scores, hypertension, hyperlipidemia, diabetes mellitus, Barthel index, BMI, and living situation in multivariable regression analyses. Conclusion: The present analyses suggest that the resilience capacity may be related to the cortical thickness in the posterior cingulate and temporal cortices in older adults. Our findings warrant further longitudinal studies to confirm the causal relationship between stress events, resilience, and brain structures. Highlights: Resilience is associated with cortical thickness of the temporal pole and the posterior cingulate cortex in older people. Resilience-related brain areas of older adults are observed in the limbic system and the inferior and medical cortices. Integrated self-awareness through the default mode network may increase the resilience capacity. Resilience in older people is likely to depend on the neural basis contributing to emotional stability.